Effects of copper vapor laser radiation on the root canal wall of human teeth: A scanning electron microscope study - Niccoli-Filho, Walter; Garcia Da Silveira, Maria Cláudia; Dias Vieira Jr., Nilson; Riva, Rudimar (SAGE Publications, 2005)
Objective: The aim of this study is to analyze the effects of copper vapor laser radiation on the radicular wall of human teeth. Materials and Methods: Immediately after the crowns of 10 human uniradicular teeth were cut along the cement-enamel junction, a chemical-surgical preparation of the radicular canals was completed. Then the roots were longitudinally sectioned to allow for irradiation of the surfaces of the dentin walls of the root canals. The hemi-roots were separated into two groups: one (control) with five hemi-roots that were not irradiated, and another (experimental) with 15 hemi-roots divided into three subgroups that were submitted to the following exposure times: 0.02,0.05, and 0.1 s. A copper vapor laser (510.6 nm) with a total average power of 6.5 W in green emission, frequency of 16.000 Hz, and pulse duration of 30 ns was used. Results: The results obtained by scanning electron microscope analysis showed the appearance of a cavity in the region of laser beam impact, with melting, recrystallization, and cracking on the edges of the dentin of the cavity due to heat diffusion. Conclusions: We determined that the copper vapor laser produces significant morphologic changes in the radicular wall of human teeth when using the parameters in this study. However, further research should be done to establish parameters that are compatible with dental structure in order to eliminate thermal damages. © Mary Ann Liebert, Inc.
Keywords: Diffusion; Irradiation; Laser beams; Lasers; Morphology; Radiation; Recrystallization (metallurgy); Scanning electron microscopy; Copper vapor; Heat diffusion; Laser radiation; Radicular walls; Copper; cementation; controlled study; copper vapor laser radiation; crystallization; dental caries; dentin; diffusion; enamel; heat; human; human tissue; laser; melting point; parameter; radiation dose; scanning electron microscopy; tooth; tooth crown; tooth root canal; Dental Pulp Cavity; Dentin; Humans; Laser Surgery; Microscopy, Electron, Scanning